Pistacia lentiscus L. fruits showed promising antimutagenic and antigenotoxic activity using both in-vitro and in-vivo test systems. Issue 15 (3rd August 2022) - Bouguellid, Ghania; Debbache-Benaida, Nadjet; Atmani-Kilani, Dina; Russo, Chiara; Lavorgna, Margherita; Piscitelli, Concetta; Ayouni, Karima; Berboucha-Rahmani, Meriem; Isidori, Marina; Atmani, Djebbar
ABSTRACT: Pistacia lentiscus L. is one of the most popular medicinal plants attributed to its beneficial properties on human health. However, few toxicogenetic studies have been carried out. Therefore, the aim of this study was to examine the potential genotoxic/antigenotoxic and mutagenic/antimutagenic properties of oil, ethyl acetate and ethanolic extracts of P. lentiscus L. fruits using in vitro the Ames and Umu assays, as well as in vivo micronucleus (MN) test. Extracts did not exert any significant mutagenic/genotoxic effects but provided protection against standard mutagenic and genotoxic agents including 2 nitrofluorene (2-NF) at 2.5 and 5 µg/ml; sodium azide at 5 and 10 µg/ml; 3-methylcholanthrene (3-MC) at 25 and 50 μg/ml; cyclophosphamide (CP) at 50 and 100 μg/ml; 4-nitroquinoline 1-oxide (4-NQO) at 0.05 µg/ml and 2-amino-anthracene (AA) at 0.2 µg/ml. Further, cytotoxicity and selectivity were examined on human hepatocarcinoma (HepG2), and MCF-7 breast cancer cell lines as well as a human normal-like fibroblast cell line (TelCOFS02MA) using MTT assay. Among all extracts, PF1 (ethanolic) showed the most significant selectivity index (SI) (HepG2:11.98; MCF7:4.83), which led to further investigations using an animal model. Oral administration of PF1 (125–1000 mg/kg b.w.) significantly decreased the number of micronucleated cells in CP -initiated (50 mg/kg b.w.) mice, while the number of micronucleated reticulocytes (MNRET), micronucleated polychromatic erythrocytes (MNPCE) or mitotic index (MI) were not markedly affected. Further, PF1 significantly enhanced catalase (CAT) and superoxide dismutase (SOD) activities in the livers and kidneys of these animals. The obtained results indicated the beneficial properties of P. lentiscus L. fruits for use in therapy against harmful effects of genotoxic and mutagenic agents. However, while promising it should be noted that the obtained results are preliminary and need to be confirmed prior to therapeutic use.